2015
DOI: 10.15288/jsad.2015.76.378
|View full text |Cite
|
Sign up to set email alerts
|

Nosologic Comparisons of DSM-IV and DSM-5 Alcohol and Drug Use Disorders: Results From the National Epidemiologic Survey on Alcohol and Related Conditions–III

Abstract: ABSTRACT. Objective: The purpose of this study was to examine prevalences and concordances between Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), and Fifth Edition (DSM-5) substance use disorders (SUDs) in a newly completed U.S. epidemiologic survey. Method: The National Epidemiologic Survey on Alcohol and Related Conditions-III surveyed 36,309 civilian, noninstitutionalized adults. SUDs were assessed using the Alcohol Use Disorder and Associated Disabilities Interview Schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 90 publications
2
26
0
Order By: Relevance
“…The Mewton and colleagues study (2011) assessed each and every symptom criterion in the 12 months prior to interview and showed an increase in the prevalence of AUD under DSM‐5 compared with DSM‐IV, whereas the current study employed a lifetime time frame and showed a slight decrease. It is notable that this pattern of findings is similar to that shown in a recent nosologic comparison of DSM‐IV and DSM‐5 alcohol and drug use disorders using data from the National Epidemiologic Survey on Alcohol and Related Conditions‐III (Goldstein et al., ). Recent research summarizing AUD symptom severity (derived through item response theory) across 34 previously published studies concluded that variability in the diagnostic instruments employed was the biggest contributor to low consistency in the rank ordering of AUD criteria severity (Lane et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…The Mewton and colleagues study (2011) assessed each and every symptom criterion in the 12 months prior to interview and showed an increase in the prevalence of AUD under DSM‐5 compared with DSM‐IV, whereas the current study employed a lifetime time frame and showed a slight decrease. It is notable that this pattern of findings is similar to that shown in a recent nosologic comparison of DSM‐IV and DSM‐5 alcohol and drug use disorders using data from the National Epidemiologic Survey on Alcohol and Related Conditions‐III (Goldstein et al., ). Recent research summarizing AUD symptom severity (derived through item response theory) across 34 previously published studies concluded that variability in the diagnostic instruments employed was the biggest contributor to low consistency in the rank ordering of AUD criteria severity (Lane et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…Comparisons of prevalence rates according to different diagnostic systems were conducted using McNemar tests of correlated proportions. Specifically, as concordance between DSM‐IV dependence and DSM‐5 SUD was maximized for alcohol when using ≥ 4 DSM‐5 SUD criteria (Compton et al., ; Goldstein et al., ), McNemar tests of correlated proportions were used to compare DSM‐IV, ICD‐10, and ICD‐11 dependence against DSM‐5 M/S use disorder (≥ 4 criteria). Exploratory comparisons of diagnostic groupings on frequency of substance use and symptom count were conducted using analysis of covariance, controlling for age and gender.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of diagnoses and symptoms, and diagnostic concordance across the classification systems were examined. Due to the substantial changes proposed for ICD‐11 dependence, and that ICD‐11 and DSM‐5 may be used concurrently, we examined prevalence and concordance of proposed ICD‐11 dependence and DSM‐5 M/S (DSM‐5 M/S is generally considered to be comparable to DSM‐IV dependence; Compton et al., ; Goldstein et al., ). We also identified sources of diagnostic switching (i.e., “loss” or “gain” of diagnostic status) for DSM‐5 M/S and proposed ICD‐11 dependence to determine sources of diagnostic disagreement.…”
Section: Classification Of Suds In Dsm‐iv Dsm‐5 Icd‐10 and Icd‐11mentioning
confidence: 99%
“…Cannabis is the most commonly used illicit drug world‐wide , and there is great controversy over the relative benefits versus adverse effects of its use . Two important factors involved in cannabis use are affect and impulsivity, both of which are implicated in theories of substance use and abuse.…”
Section: Cannabis Use Affect and Impulsivity In Daily Lifementioning
confidence: 99%